Esophagogastric Leiomyoma Therapeutic Approach: A Case Report and Literature Review - El Hattabi, Khalid; Ettaoussi, Abdelhak; Benzidane, Kamal; El Bakouri, Abdellillah; Bouali, Mounir; Khadija, Kamal; Abdessamad, Majd (British Journal of Healthcare and Medical Research, 2025)
Gastric leiomyomas are uncommon benign tumors that occur in only 2.5% of all gastric neoplasms. Although often asymptomatic, larger or strategically located tumors can cause symptoms such as gastrointestinal bleeding or postprandial discomfort. Diagnosis requires a combination of imaging, endoscopic evaluation and histopathology analysis. Treatment is primarily surgical, with laparoscopic approaches being preferred due to their minimally invasive nature and reduced risk of postoperative complications.